Periinterventional cardiovascular risk and the methods for its reduction in coronary heart disease patients undergoing percutaneous coronary intervention - K. A. Nazarova; O. V. Khilkevich; G. K. Kiyakbaev; Zh. D. Kobalava; V. S. Moiseev (Кардиоваскулярная терапия и профилактика)
Such periinterventional complications of percutaneous coronary intervention (PCI) as myocardial infarction (MI), “no-reflow/slow-flow” phenomenon, and stroke, affect long-term survival. Therefore, their risk should be effectively stratified and reduced. The existing approaches for predicting the risk of periinterventional complications are typically focussed on assessing the fatal outcome probability and do not consider modifiable risk factors, which restricts their use to evaluation of PCI benefits and risk only. Periinterventional statin therapy reduces the risk of periinterventional MI both in patients with stable angina and individuals with acute coronary syndrome. This beneficial action could be related to anti-inflammatory, antioxidant, antithrombotic, NO- and immunomodulating effects of statins. The evidence on cardioprotective effects of periinterventional beta-blocker therapy is contradictory for PCI patients. Existing data on the link between beta-blocker treatment and increased risk of “slow flow” phenomenon, coronary artery spasm, heart failure, and arterial hypotension point to the need for optimisation of the pulse-reducing component of pharmaceutical PCI support. One of the promising methods for solving this problem could be administration of ivabradine – a medication with confirmed anti-ischemic and antianginal action, but no effects on myocardial contractility or blood pressure level.